Using Visual Cryptography and hash function for Fragile Watermarking to Detect Electronic Document Forgery - Hussein, Hala k.; Muhajjar, Ra'ad A.; Mahdi, Bashar S (Iraqi Journal of Science, 2023)
Recent developments in technology and the area of digital communications have rendered digital images increasingly susceptible to tampering and alteration by persons who are not authorized to do so. This may appear to be acceptable, especially if an image editing process is necessary to delete or add a particular scene that improves the quality the image. But what about images used in authorized governmental transactions? The consequences can be severe; any altered document is considered forged under the law and may cause confusion. Also, any document that cannot be verified as being authentic is regarded as a fake and cannot be used, inflicting harm on people. The suggested work intends to reduce fraud in electronic documents using a novel generator. It employs modern encryption methods to conceal the data represented by the watermark and hide it secretly inside the document so that it is easy to check for signs of counterfeiting; thus, allowing for the discovery of forged papers